A dinâmica discursiva na sala de aula e a apropriação da escrita - Maria do Socorro Alencar Nunes Macedo (1998)
This study analyzes the process by wich children appropriate ortography in the context of classroom discoursive dynamics.The fact of having chosen to condut this research in the classroom has allowed us to analyze the process of verbal interaction between teachr and student and amongst students themselves, thus revealing different elements which make up pedagogical work. In order to analyze data, we will dra mainly on the theoreticl constructs of historical-cultural psychology and on those of lnguae studies, specilly on Bakhtin's enunciation theory. According to these references, social interaction proceses generate Knowledge through mediation of ohers and thouh language. We have highlihted vídeo ecorded teaching-lerning processes which eveal evidence of intermental and inramental actiities elaborated by subjects in interlocution processes with their pers and teacher, as they raise questions concrning written language features. Through this analisis our aim is to contribute to questions concerning the elabotion of knowledge in the clasrrom this offering elements which may contribute to the eduction of those involved in teaching how to read and rite.